2021
DOI: 10.3390/cells10092338
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Heterogeneity in Development and Wound Healing

Abstract: The vasculature is comprised of endothelial cells that are heterogeneous in nature. From tissue resident progenitors to mature differentiated endothelial cells, the diversity of these populations allows for the formation, maintenance, and regeneration of the vascular system in development and disease, particularly during situations of wound healing. Additionally, the de-differentiation and plasticity of different endothelial cells, especially their capacity to undergo endothelial to mesenchymal transition, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 132 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…Formation of new blood vessels through vasculogenesis and further expansion of the network by angiogenesis happens through coordinated cell proliferation, migration, matrix attachment and remodelling, processes critically dependent on the actin cytoskeleton. Several recent reviews highlight the steps involved in angiogenic sprouting and the key molecular players involved in it ( Eelen et al, 2020 ; Gurevich et al, 2021 ). Recent bulk and single cell RNA seq experiments reveal that indeed capillary endothelial cells exhibit enormous diversity between vascular beds with gene signatures unique to the tissues they supply ( Eelen et al, 2020 ; Gurevich et al, 2021 ; Paik et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of new blood vessels through vasculogenesis and further expansion of the network by angiogenesis happens through coordinated cell proliferation, migration, matrix attachment and remodelling, processes critically dependent on the actin cytoskeleton. Several recent reviews highlight the steps involved in angiogenic sprouting and the key molecular players involved in it ( Eelen et al, 2020 ; Gurevich et al, 2021 ). Recent bulk and single cell RNA seq experiments reveal that indeed capillary endothelial cells exhibit enormous diversity between vascular beds with gene signatures unique to the tissues they supply ( Eelen et al, 2020 ; Gurevich et al, 2021 ; Paik et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews highlight the steps involved in angiogenic sprouting and the key molecular players involved in it ( Eelen et al, 2020 ; Gurevich et al, 2021 ). Recent bulk and single cell RNA seq experiments reveal that indeed capillary endothelial cells exhibit enormous diversity between vascular beds with gene signatures unique to the tissues they supply ( Eelen et al, 2020 ; Gurevich et al, 2021 ; Paik et al, 2020 ). The two non-muscle actin isoforms (β actin and γ actin) form spatially segregated structures with differences in the β/γ ratio between different cell types ( Dugina et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, their functional properties and heterogeneity in diabetes remain uncharacterized. Studies have shown that ECs have basal heterogeneities in structure and function in different tissues and organs in the physiologic state (Gurevich et al ., 2021; Pasut et al ., 2021; Ricard et al ., 2021); this makes therapeutic targeting of the endothelium challenging. However, for drug discovery, an understanding of the molecular regulators of EC function in the pathophysiological state is essential to be able to successfully interfere with the diabetic disease without affecting normal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have revealed the importance of paracrine signalling in controlling cellular heterogeneity and highlighted using multicellular populations such as organoids to better mimic native pathophysiological responses (Shalek et al ., 2014). Additionally, vascular organoids exclude the complexity and variations that come from the organ itself or other non-vascular cells but have the essential vascular cells vital for blood vessel function allowing straightforward recapitulating and capturing pathophysiological changes in vitro (Kalucka et al ., 2020; Gurevich et al ., 2021; Pasut et al ., 2021; Ricard et al ., 2021). However, how disease-specific phenotypes are displayed in iPSCs-derived vascular organoids has not been fully delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond endothelialization and neointima production, PCs, therefore, also have regulatory functions as they release paracrine mediators, including the vascular endothelial growth factor or the hepatocyte growth factor that are involved in the vascular repair processes by activating both resident endothelial cells and fibroblasts to produce an extracellular matrix [54]. Although proliferation of SMCs and production of the intercellular matrix are the main drivers of neointima formation and restenosis following percutaneous interventions, other types of PCs have a regulatory effect on these cells.…”
Section: The Role Of Progenitor Cellsmentioning
confidence: 99%